Breeding biology and feeding ecology of Black guillemots - Petersen, Æ; Petersen, Aevar (1981)
﻿ Since 1974 a population study of Black Guillemots has been conducted on Flatey Island, NW Iceland. The main aspects are summarized below. Population numbers and distribution. The population has been censused several years, also those of 20 islets near Flatey. Information was collected on past status. Great changes have occurred since turn of the century. Last major change began in 1967; the population started increasing of such a scale that it can only have resulted from massive immigration. These changes are thought to be due to rats and Mink. Attendance and population structure. Data was gathered on timing of spring return to nesting areas, status of attending birds, sex ratio, area and nest-site fidelity, pair-bond maintenance, and post-breeding departure. Special attention has been given to the problem of censusing birds attending nesting areas. Breeding biology. Breeding biology variables were quantified and studied on a seasonal basisj;timing of laying, clutch size, interval between eggs, egg size, reproductive output, lengths of incubation and nestling periods. Supernormal clutch and brood experiments were conducted. I looked at length of replacement time of lost clutches, factors influencing timing of laying, its effect and that of clutch and egg size on breeding performance. Egg and chick losses were analyzed. Many interesting population phenomena seem to have been associated with the unusually rapid population increase. Feeding ecology. Analyses were made of prey taken, feeding rhythm and areas, and factors influencing feeding rate and prey selection. Some information was collected on share of the sexes in feeding chicks, and kleptoparasitism. Study was made of chick growth, fledging condition and postfledging survival. Population dynamics. About 3300 birds were ringed, providing basis for determining age at maturity, adult survival, and mortality. Pre-breeding survival was calculated using data from ringing schemes. A population model was constructed for the population, showing magnitude of immigration. Ringing provided data on dispersal.